(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Geographical information systems (GIS) are computer-based systems designed specifically to facilitate the digital storage, retrieval, and analysis of spatially referenced environmental data. Coupled with ecological modelling, GIS can provide significantly increased opportunities for detailed environmental resource inventory and analysis and show considerate promise for extensive use in nature conservation. The paper introduces these two concepts and discusses the role of GIS-based modelling in nature conservation focusing on the predictive models for species occurrence, plant community occurrence and habitat suitability. The importance of Digital Elevation Models and their derived properties in these ecological studies is explained. Emphasis is placed on empirical or inductive modelling based on field observations. The generic steps of empirical modelling are described and demonstrated by a case study in Lefka Ori, Crete, Greece. Tools such as fuzzy mapping and geo-statistics have a potential role to play in improving the level of information and therefore in the understanding of species and plant community distribution.